Students’ Ability of Using Simple Present Tense on Descriptive Text at Seventh Grade of Junior High School Laboratorium Jambi City - Butar Butar, Putri Anggie Ayu; Ismiyati, Yanti; Dinata, Ridho Praja (JELT: Journal of English Language Teaching, 2024)
The ability of students to understand the learning material is important, especially in understanding the simple present tense in descriptive text. This research is aimed to find out how far the students' ability to understand the simple present tense in descriptive text. This research uses quantitative as a research design and descriptive quantitative as a research approach. This research took a population of seventh graders at SMP Laboratorium Jambi City in the 2023/2024 academic year and the sample was all students in class VII in the 2023/2024 academic year. This research uses a multiple-choice test given to the respondents as a research instrument, and then the results of the test are assessed and analyzed. The technique of collecting data was using the test. The technique of data analysis was using the mean formula. This research found that the average value of the test obtained is 49.66. As a result, 2 students received the predicate "good", 8 students received the predicate "moderate", and 5 students received the predicate "poor". In conclusion, the student's ability to understand simple present tense in descriptive text is moderate level.Keywords: Students’ ability, simple present tense, descriptive text